2008
DOI: 10.1007/s10584-008-9437-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan

Abstract: Researchers of climate change have suggested that climate change and variability has a significant influence on the epidemiology of infectious diseases, particularly vector-borne diseases. The purpose of this study is to explore how climate conditions and the dengue fever epidemic in Taiwan are related and to estimate the economic impact of climate change on infectious diseases. To achieve these objectives, two different methods, one involving the Panel data model and the other the Contingent Valuation Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 18 publications
0
28
2
Order By: Relevance
“…As another extreme example, Liu et al [18] estimated the WTP to reduce the risk of infection and death from severe acute respiratory syndrome (SARS) in Taiwan and found that the values per statistical life ranged from 3 to 12 million US dollars. Their WTP estimates are higher than those of Tseng et al [11] and this study because of the higher mortality rate associated with SARS. Comparing with other diseases such as the food-borne diseases Campylobacteriosis or Salmonellosis, Goldberg and Roosen [19] applied CVM and found that an individual's WTP ranged from US$2.98 for a risk reduction of 40% for Campylobacteriosis or Salmonellosis to US$5.88 for a risk reduction of 80% for Salmonellosis and a risk reduction of 40% for Campylobacteriosis.…”
Section: Modeling Design For the Cvmcontrasting
confidence: 85%
See 1 more Smart Citation
“…As another extreme example, Liu et al [18] estimated the WTP to reduce the risk of infection and death from severe acute respiratory syndrome (SARS) in Taiwan and found that the values per statistical life ranged from 3 to 12 million US dollars. Their WTP estimates are higher than those of Tseng et al [11] and this study because of the higher mortality rate associated with SARS. Comparing with other diseases such as the food-borne diseases Campylobacteriosis or Salmonellosis, Goldberg and Roosen [19] applied CVM and found that an individual's WTP ranged from US$2.98 for a risk reduction of 40% for Campylobacteriosis or Salmonellosis to US$5.88 for a risk reduction of 80% for Salmonellosis and a risk reduction of 40% for Campylobacteriosis.…”
Section: Modeling Design For the Cvmcontrasting
confidence: 85%
“…To estimate the effects of climate change on the mortality of cardiovascular diseases in Taiwan, a two-step estimation approach is applied. Such an estimation procedure is similar to that in the study by Tseng et al [11]. As the first step, the relationship between the number of deaths from cardiovascular diseases and various climatic conditions needs to be established and estimated.…”
Section: Model Equation Specificationsmentioning
confidence: 99%
“…The estimated coefficients give information on the relationship between observed malaria cases, temperature and precipitation. The theoretical model follows the analysis in Li and Racine as well as Tseng et al [28,31] and is specified as follows: yit=f(Xit)+βZit+αi+uit,t=1,,Tandi=1,,Nwhere y it is the natural log of the number of reported malaria cases per 1,000 people in country i at time period t; X it is a vector of climate variables that includes temperature, precipitation and a measure of climate variability; Z it is a vector of socio-economic control variables that includes population density, per capita gross domestic product, inequality index, per capita healthcare expenditure and number of hospital beds per 1,000 people; α i are unobserved individual country effects and u it is an idiosyncratic error term. The function f , the coefficients β and the unobserved country effects α i are all parameters to be estimated.…”
Section: Model Specificationsmentioning
confidence: 99%
“…Recent studies using SP methods to assess the WTP of the general population for the total economic value of climate change mitigation policies include Berk and Fovell (1999), Roe et al (2001), Berrens et al (2004), Li et al (2004), Nomura and Akai (2004), Li et al (2005), Hidano and Kato (2007), Longo et al (2008) and Tseng et al (2009). All of these studies have focused on the global benefits of GHG emissions reductions, and none of them has looked at ancillary benefits induced by climate change policies.…”
mentioning
confidence: 99%